2020
DOI: 10.1038/s41467-020-15772-1
|View full text |Cite
|
Sign up to set email alerts
|

High temperature rise dominated cracking mechanisms in ultra-ductile and tough titanium alloy

Abstract: Extensive use of titanium alloys is partly hindered by a lack of ductility, strain hardening, and fracture toughness. Recently, several β-metastable titanium alloys were designed to simultaneously activate both transformation-induced plasticity and twinning-induced plasticity effects, resulting in significant improvements to their strain hardening capacity and resistance to plastic localization. Here, we report an ultra-large fracture resistance in a Ti-12Mo alloy (wt.%), that results from a high resistance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 50 publications
(71 reference statements)
0
22
0
Order By: Relevance
“…is finding also shows that the dynamic loading is similar to the hot rolling process, which is a comprehensive process of heat power. When a certain strain is reached, adiabatic shear band may appear, which is a vantage position for recrystallization nucleation [28,29], leading to the formation of recrystallization texture or the increase of its intensity.…”
Section: Resultsmentioning
confidence: 99%
“…is finding also shows that the dynamic loading is similar to the hot rolling process, which is a comprehensive process of heat power. When a certain strain is reached, adiabatic shear band may appear, which is a vantage position for recrystallization nucleation [28,29], leading to the formation of recrystallization texture or the increase of its intensity.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study [12], it was shown that the very large ductility of Ti-12Mo results from a large resistance to damage nucleation. Many interfaces are created by the different plasticity mechanisms activated in Ti-12Mo, including both TRIP and TWIP effects, resulting in a rapid nanostructuration of the microstructure, already at a strain level corresponding to the true uniform strain [12]. However, no void nucleates until the formation of a thin localized shear band at the end of the plastic deformation.…”
Section: Fracture Of Flat Tensile Specimensmentioning
confidence: 99%
“…The formation of these shear offsets as well as their final propagation result probably from the exhaustion of the strain hardening capacity of the alloy. The alloy presents an impressive capacity to store the deformation-induced defects during its deformation, resulting in a nanostructure with a very large density of stored defects inside the microstructure [12].…”
Section: Fracture Of Flat Tensile Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous works have tried to develop new materials by introducing physical or chemical bonds between two different materials such as composites and alloys, or tuning microstructures of single materials. [1][2][3][4][5][6] The lattice structure, especially, inspired by the unit cell of crystalline materials in nature, is one of the most lightweight structures compared to conventional engineering materials. 7,8 With the recent development of precise additive manufacturing processes, much work has been devoted to understanding the relationship between microstructure and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%